How Can We Read Out Life Quality Assessments from the Official Socio-Economic Data on Polish Municipalities? - Owsiński, Jan W. (Czy można ocenić jakość życia na podstawie oficjalnych danych statystycznych z poziomu gminy?, 2009)
In the research on sustainable development at the municipal level in Poland and its indicators, conducted within the project ANAGMIS, one of the themes concerns life quality, as perceived through the municipality-level data. The paper, first, refers to the broadly conceived “economic” and “civilisational” aspects of the statistical description of municipalities. After having shown some of the extreme cases for Poland, we look at the proxy for the subjective evaluation of life quality, directly based on migration and migration balance (“voting with the legs”). This proxy is confronted with other descriptive variables in the first stage of an attempt of building the model of migration-based life quality assessment model. The conclusions from this stage of work, meant to direct the further study, close the paper.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 73, s. 50-63